Discipline in Education, and its relationship with Students’ Academic Achievement at University Level - Munir, Hina; Iqbal, Maria; Munawar, Uzma (Pakistan Journal of Humanities and Social Sciences, 2024)
The purpose of the research was to know the relationship of discipline in education and students’ academic achievement at university level. The study’s population of concern included all social sciences students from two universities in Multan district (Bahauddin Zakariya University and The Women University). Sample of the study was consisted of 300 students. Just the students of social sciences was selected from these universities, and 25 students were chosen from each department. Questionnaire was developed for students which contains 26 items and five point likert was used for scoring. Data were entered on SPSS sheet after the completion of data collection. Various statistical methods were applied to obtain the findings about the student’s reactions like percentage, mean, frequency and standard deviation was used to apply and examine the relationship of discipline in education with student academic achievement. After complete analysis of data it was found that the majority of the participants believe that discipline in education helps student’s to complete their assignments on time, arrive on time for class and participates in every class discussions.